Characterization and Simulation of a Magnetized Sample - Linnert, Michael; Lerch, Reinhard; Sutor, Alexander; Rupitsch, Stefan (PROCEEDINGS – AMA Conferences 2017 AMA Conferences 2017 Nuermberg Exhibition Centre, Germany 30.5. – 1.6.2017 SENSOR 2017 18th International Conference on Sensors and Measurement Technology IRS2 2017, 2017)
For several decades, magnetic sensors have been exploiting the nonlinear relation between the mag-netic field strength and the magnetic flux density. Whereas strong saturation effects were most relevant in the past, today energy consumption of modern sensors plays an increasingly important role. Recent semihard magnetic materials concern this issue by retaining a significant magnetic flux density even when all excitation currents are turned off. Nevertheless, in contrast to classical hard magnets, it is relatively easy to commutate them. With sensor development cycles becoming shorter, there is an in-creasing demand for accurate numerical models concerning hysteresis. In this contribution, we present a new combination of scalar and vector material characterization techniques to compute the remanent magnetic field of a magnetized sample by static finite element (FE) simulations. Vacuumschmelze offers a suitable semihard magnetic material with a coecivity field around 2kA/m that is available as thin stripes. In a first step, the Sensorvac material will be characterized to obtain meaningful material properties required for simulations. With material parameters having been identified, the remanent magnetic field of the magnetized sample will be computed. As it is revealed, simulation results coincide very well with laboratory measurements. In future, the model can be applied to design complex sensors.
Keywords: FEM; magnetics; hysteresis; material properties; remanent field

Dynamic Offset Correction of Electromagnetic Flowmeters - Linnert, Michael; Mariager, Simon Oddson; Rupitsch, Stefan; Lerch, Reinhard (IEEE Transactions on Instrumentation and Measurement, 2018)
This contribution addresses the electrochemical voltage drift of electromagnetic flowmeters. We will extend the conventional discrete time alternating field method to continuous operation. A Kalman filter, based on a state space model of the sensor, will be developed to separate the flow-proportional signal from the noisy voltage drift of the electrodes. The new algorithm facilitates the processing of flow information rarely used today, i.e., longer intervals of the electrode voltage during times of stable magnetic field. The actually processed time interval of the electrode signal will be extended considerably. Thereby, a lower energy consumption and an increased accuracy can be achieved. The measurement error of the new method will be demonstrated to be less addicted to temporal flow variations. Measurements show a similar accuracy, but with a significantly reduced energy demand. A prototype with a field offset provided by permanent magnets is set up to evaluate its energy consumption. Offline signal processing predicts an 80% lower power demand compared to conventional flowmeters.<br
Keywords: accuracy; data fusion; electromagnetic flowmeter (EMF); energy consumption; kalman filter; signal processing; state space

Dynamic Offset Correction of Electromagnetic Flow Meters - Linnert, Michael; Mariager, Simon; Rupitsch, Stefan; Lerch, Reinhard (2018 IEEE International Instrumentation and Measurement Technology Conference (I2MTC 2018) Proceedings, 2018)
This contribution addresses the electrochemical voltage drift of electromagnetic flow meters. We will extend the conventional discrete time alternating field method to continuous operation. A Kalman filter, based on a state space model of the sensor, was developed to separate the flow-proportional signal from the noisy voltage drift of the electrodes. The new algorithm allows to process flow information rarely used today, i.e., the electrode voltage during times of stable magnetic field. Thereby a lower energy consumption and an increased accuracy can be achieved. Compared to conventional signal processing, the performance of the new method is far more independent of the transient behavior of the actual flow. Measurements show a comparable accuracy, but with a significantly reduced energy demand. Off-line signal processing let expect a theoretical power reduction factor around 15
Keywords: electromagnetic flow meter; energy consumption; accuracy; Kalman filter; data fusion; state space; signal processing

Magnetisch-induktive Durchflussmessung mittels remanentem Magnetismus - Linnert, Michael; Mariager, Simon; Lerch, Reinhard (Technisches Messen, 2019)
Magnetisch-induktive Durchflusssensoren zeichnen sich durch lange Wartungsintervalle aus, sind jedoch auf die Zuführung elektrischer Leistung zur Erzeugung des für die Messung benötigten magnetischen Wechselfelds angewiesen. In jüngster Zeit gibt es Bestrebungen Sensoren kabellos zu betreiben. Die Minimierung des Leistungsbedarfs des Sensors gewinnt so zunehmend an Bedeutung, um eine lange Betriebszeit des Messwertgebers sicherzustellen. In diesem Beitrag wird deshalb ein magnetisch remanentes Material hinsichtlich seines Energieeinsparpotentials für die magnetisch-induktive Durchflussmessung untersucht. Im Gegensatz zur üblichen Felderzeugung mittels Elektromagneten wird nur während der kurzen Umpolzeiträume elektrische Leistung benötigt. Danach bleibt das Magnetfeld auch ohne weitere Zuführung elektrischer Leistung konstant und kann zur Durchflussmessung herangezogen werden. Anders als beispielsweise Ferritmagnete lassen sich remanente Magnetmaterialien jedoch unter geringerem Energieaufwand umpolen, was sie für die Erzeugung magnetischer Wechselfelder prädestiniert. Wie ein Sensor auf Basis remanenter Materialien dimensioniert werden sollte, damit ein für die Messung ausreichendes Magnetfeld unter minimalen Verlusten erzeugt wird, ist eine der Kernfragen dieses Beitrags. Dazu wird ein Prototyp mithilfe eines Modells ausgelegt und messtechnisch untersucht. Die Ansteuerung des Sensors erfolgt über eine eigens entwickelte Logikschaltung. Es konnte gezeigt werden, dass die Messgenauigkeit unabhängig von der Art der Felderzeugung erhalten bleibt. Für niedrige Feldwechselraten kann der geringe Leistungsbedarf remanenter Magnetmaterialien bestätigt werden.<br
Keywords: Durchflussmessung; Magnetisch; Induktiv; Remanenz; Leistungsbedarf